1465 Anaesthetic Preferences in a Tertiary Hand Surgery Unit & Aetiology of Hand Trauma Presentations During the First UK lockdown: Lessons for the Future. (12th October 2021) - Khoury, A; Thomson, D; Jones, M
Abstract: Introduction: Our tertiary plastics unit serves a 4.3 million population in the South East, providing a seven-day hand trauma service. Our aim was to assess differences in quantity and aetiology of hand trauma during the April 2020 lockdown compared with the equivalent period in 2019, and our ability to reduce risk by carrying out more procedures under local anaesthetic. Method: Retrospective notes review for hand trauma surgery patients in April 2020 (3 weeks in first UK lockdown), with a comparative period in April 2019. Fisher's Exact Test was applied to assess for difference in method of anaesthetia, injury location (workplace vs home) and DIY versus non-DIY aetiology. Results: 2020 group: n = 165. 2019: n = 239. (31% reduction). Mean age 45 during lockdown vs 49 in 2019. There was significant reduction in the proportion of workplace injuries in 2020 (22% vs 29%), but the proportion of power tool injuries was similar (31.6% 2020 vs 26.6%). DIY injuries increased significantly (33.5% versus 9.2%). Use of local anaeshesia including increased significantly in our unit (84.2% vs 66.1% 2019) with reduction in use of regional and general anaesthesia. Conclusions: Caseload somewhat reduced during lockdown. Fewer injuries occurred in the workplace. Our unit made good use of local anaesthetic techniques to avoid regional anaesthesia (and risk of need for GA conversion) wherever possible. Public safety warnings existed (BAPRAS and BSSH), but perhaps were less publicly available than desirable. Improving awareness further could reduce trauma surgery burden as we enter a third wave of the pandemic.